Development of Physical-Motor Activities Training Package and Evaluation of its Efficacy on Executive Functions in Children with Attention Deficit / Hyperactivity Disorder - Shahnaz Hashemi malekshah; Hamid Alizadeh; Saeed Rezayi; Mohammad Asgari (مجله علوم روانشناختی, 2021)
Background: Various studies revealed the effectiveness of physical activity training programs on executive functions in the children with attention deficit-hyperactivity disorder (ADHD). Hence, examining the impact of the interventional strategies of physical and motor activities on executive functions in the children with ADHD has had some limitations. Aims: This study aimed to develop a training package of Physical-Motor Activities and evaluate its impact on executive functions of children with ADHD. Methods: The present study was applied in terms of purpose and the method of combined type (qualitative and quantitative) as the qualitative part of treatment plan and the quantitative part of quasi-experimental method with unbalanced control group design and follow-up session. Statistical population in the qualitative section is based on the theories of Barkley (2015) and includes experts in the field of child motor skills and research published in prestigious journals from 1390 to 1399 for Persian articles and from 2000 to 2020 for the English articles in the field of motor interventions for children with ADHD. The quantitative part included all boys with ADHD aged 7-12 years in the primary schools of the 16th district of Tehran. For sampling among the schools in District 16, four schools were selected as available, and 30 children with ADHD were identified in those schools and then randomly assigned to two experimental and control groups (each group including 15 children). The instruments used in this study were Diagnostic Questionnaires of ADHD (APA 2013) and BRIEF for the executive functions (Gioia et al., 2000). The children in the experimental group participated in the training program in 24 sessions of 60 minutes. Data were analyzed using a mixed analysis of variance. Results: In the qualitative part, research results showed that the training package had sufficient content validity in the opinion of experts. In the quantitative part, the results manifested that by controlling the pre-test, the training package of physical-motor activities caused a significant improvement in the components of attention, inhibition, and working memory (p <0.001) in the experimental group compared to control group. However, there was no change in the planning and organizing components of the experimental group compared to control group (p> 0.001). Conclusion: Overall the result of the present study showed that physical-motor activities training program has positive effects on executive functions of children with ADHD.